The Excited‐State Creutz–Taube Ion. (18th October 2022) - Pieslinger, German E.; Ramírez‐Wierzbicki, Ivana; Cadranel, Alejandro
Abstract: The excited‐state version of the Creutz–Taube ion was prepared via visible light excitation of [(NH3 )5 Ru II ( μ ‐pz)Ru II (NH3 )5 ] 4+ . The resulting excited state is a mixed valence {Ru III–δ ( μ ‐pz⋅ − )Ru II+δ } transient species, which was characterized using femtosecond transient absorption spectroscopy with vis‐NIR detection. Very intense photoinduced intervalence charge transfers were observed at 7500 cm −1, revealing an excited‐state electronic coupling element HDA =3750 cm −1 . DFT calculations confirm a strongly delocalized excited state. A notable consequence of strong electron delocalization is the nanosecond excited state lifetime, which was exploited in a proof‐of‐concept intermolecular electron transfer. The excited‐state Creutz–Taube ion is established as a reference, and demonstrates that electron delocalization in the excited state can be leveraged for artificial photosynthesis or other photocatalytic schemes based on electron transfer chemistry. Abstract : The Creutz–Taube ion was prepared as an excited state that includes a bridging pyrazine radical anion. It features an intense photoinduced intervalence charge transfer band, which allowed to directly address electronic delocalization and electronic coupling in the excited state. This species is competent for photoinduced electron transfer, illustrating the potential of photoinduced mixed valence species for photocatalysis.